Relationship between malnutrition-inflammation syndrome and ultrafiltration volume in continuous ambulatory peritoneal dialysis patients. - Nantawan Tinroongroj (2018)
Malnutrition inflammation syndrome may contribute to a change of peritoneum, leading to high peritoneal membrane transport, peritoneal albumin loss, and increased glucose uptake into systemic circulation and decreased ultrafiltration (UF) volume. Fluid overload is a common problem among CAPD patients which has an effect on morbidity and mortality in these patients. The present study was designed as a pilot to find out a correlation between malnutrition and UF volume in CAPD patients. A cross-sectional study was comducted in 42 stable CAPD cases at CAPD clinic, Maharaj Chiang Mai Hospital. Subjective global assessment score (SGA), malnutrition inflammation score (MIS), and laboratory values were utilized to identify nutritional and inflammatory status. Peritoneal equilibration test (PET) was performed to measure UF volume while bioelectrical impedance assay was determined to measure extracellular fluid volume (ECF), lean body mass (LBM), lean fat mass, and fluid status. Of 42 CAPD patients, 30 subjects were classified to have normal nutritional status while 12 patients were categorized to have malnutrition. Only 1 patient was classified to have malnutrition inflammation syndrome. MIS scores and serum albumin were significantly different between 2 groups (p < 0.001). PET-UF volume was significantly decreased in the malnutrition group (p < 0.05), especially when serum albumin was less than 3.0 g/dl. PET-UF volume was reduced 137.44 ml for every 1 g/dl of serum albumin below 3.0 g/dl. Residual renal function (RRF) was also significantly reduced in malnutrition group (p < 0.05). Malnutrition, decreased RRF and decreased UF volume led to ECF expansion, hypertension, and fluid overload. Other factors that were correlated with UF volume were ACEI and/or ARB use (p < 0.05) and total protein loss per day (p < 0.05). There was a significantly positive correlation between malnutrition and reduction of UF volume. Other factors that were correlated with UF volume were ACEI and/or ARBS use and total protein loss per day.